Analisis Tindak Pidana Melakukan Perbuatan Kekerasan Fisik dalam Lingkup Rumah Tangga Ditinjau dari Pasal 44 Ayat 1 Undang-Undang No. 23 Tahun 2004 Tentang Penghapusan Kekerasan dalam Rumah Tangga (Perkara No. 593/Pid.Sus/2021/PN JKT.BRT) - Luki Pratama Putra; Zaenal Arifin; Tubagus Ahmad Suhendar (Jurnal Hukum dan Demokrasi (JHD), 2023)
Criminal Laws are Laws regarding Criminals. The word "criminal" means things that are "criminalized", that is, things that are assigned to an individual by the ruling agency as things that are unpleasant to him and also things that are not bestowed on a daily basis. Of course there is a reason for delegating this punishment and this reason should have something to do with a situation, in which a person in question acts badly. So the element of "punishment" as a retribution is implied in the word "criminal". Starting from the problems raised above, the purpose of this research is to socialize Law no. 23 of 2004 regarding the Elimination of domestic violence, not all of them are criminal complaints. This type of research is descriptive research. Data obtained from library research were analyzed qualitatively and presented descriptively. the public prosecutor believed that the violence committed by the defendant against the victim did not cause any physical damage to the victim. the judge considered that he had never been sentenced, was polite, admitted his actions frankly and regretted his actions.